2020
DOI: 10.1155/2020/5057123
|View full text |Cite
|
Sign up to set email alerts
|

Regulation on Calcium Oxalate Crystallization and Protection on HK-2 Cells of Tea Polysaccharides with Different Molecular Weights

Abstract: The regulation on calcium oxalate (CaOx) crystallization and protective effect on human proximal tubular epithelial cells (HK-2) of four green tea polysaccharides (TPSs) with molecular weights of 10.88 (TPS0), 8.16 (TPS1), 4.82 (TPS2), and 2.3 kDa (TPS3) were comparatively studied. XRD, Fourier transform infrared spectroscopy, and scanning electron microscopy results revealed that TPS1, TPS2, and TPS3 can increase the percentage of the dihydrate crystalline phase in CaOx crystals and reduce the size of CaOx mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…The diffraction peaks at crystal plane spacing d = 0.593, 0.364, 0.296, and 0.235 nm belong to the , (020), , and (130) crystal planes of calcium oxalate monohydrate (COM), respectively. The peaks at d = 0.617, 0.441, 0.277, and 0.224 nm belong to the diffraction peaks of (200), (211), (411), and (213) crystal planes of calcium oxalate dihydrate (COD), respectively [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The diffraction peaks at crystal plane spacing d = 0.593, 0.364, 0.296, and 0.235 nm belong to the , (020), , and (130) crystal planes of calcium oxalate monohydrate (COM), respectively. The peaks at d = 0.617, 0.441, 0.277, and 0.224 nm belong to the diffraction peaks of (200), (211), (411), and (213) crystal planes of calcium oxalate dihydrate (COD), respectively [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, ν as (COO − ) gradually shifts from 1624 cm −1 to 1644 cm −1 and ν s (COO − ) gradually shifts from 1320 cm −1 to 1329 cm −1 , indicating that the COM percentage in the CaOx crystal continuously decreases, while the COD percentage gradually increases. Given that the ν as (COO − ) and ν s (COO − ) of COD are 1644 and 1329 cm −1 [ 41 , 43 ], respectively, the blue shift values of ν as (COO − ) and ν s (COO − ) depend on the percentage of COD in the mixture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High oxalate concentrations have been shown to increase the production of reactive oxygen species in renal tubular epithelial cells, leading to endothelial injury and apoptosis, which plays an important role in the formation of kidney crystals [14,30]. Previous studies found that oxalate treatment increased the levels of LDH, H 2 O 2 , MDA, and ROS in HK-2 cells, which indicated the activation of oxidative stress [31][32][33]. Consistent with the findings of urolithiasis studies, we found that oxidative stress was activated in uremic atherosclerotic mice with hyperoxalemia as well.…”
Section: Discussionmentioning
confidence: 97%
“…Zhao et al [11] showed that tea polysaccharides (TPS0, TPS1, TPS2, and TPS3) with Mws of 10.88, 8.16, 4.82, and 2.3 kDa, respectively, could inhibit the adhesion of calcium oxalate monohydrate (COM) to human renal proximal tubular (HK-2) cells, and TPS2 with moderate Mw had the best protective effect. In addition, TPS with lower molecular weight have a better ability to increase the percentage of the dihydrate crystalline phase in CaOx crystals and reduce the size of CaOx monohydrate crystals [12].…”
Section: Introductionmentioning
confidence: 99%